Design and Development of an iOS-Based AAC Application to Assist Nonverbal Autistic Children in Communication - Nicoline Odelia, Lisandra; Paramita, Adi Suryaputra (Politeknik Negeri Batam, 2025)
The treatment of children with Autism Spectrum Disorder (ASD) in Indonesia is still very concerning. The lack of competent educators and therapists means that ASD children in Indonesia show slow development. Another limitation in Indonesia is the common view that children should be able to speak verbally, so many children with ASD are forced to undergo speech therapy, including tongue massage and other methods. Unfortunately, this approach often hinders their development, especially for children with non-verbal tendencies. This research aims to develop an Augmentative and Alternative Communication (AAC)-based application in Indonesian to help ASD children communicate with their surroundings. The method used is Challenge-Based Learning (CBL), which involves ASD therapists in Indonesia directly in the app development process. With the involvement of experts, the app was designed to fit the needs of ASD children based on practical and clinical considerations. The results showed that ASD children responded well and could use the AAC board effectively, optimizing the communication process in ASD children's learning.